Environmental Reporting: Four Ways Manufacturing Companies Should Aware - Cris Kuntadi (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
The purpose of this research is to examine the effect of firm size, profitability, leverage on environmental disclosure with competitive advantage as moderation. The research period is 3 years starting from 2019 to 2021. There are 64 manufacturing companies listed on the Indonesian stock exchange. sample selection using purposive sampling method. Hypothesis testing is done by using panel data regression analysis. The results of the study indicate that company size has a positive effect on environmental disclosure. Profitability, leverage, and competitive advantage have no effect on environmental disclosure. Competitive advantage is not able to moderate the relationship between company size and environmental disclosure. Competitive advantage is not able to moderate the relationship between profitability and environmental disclosure. Competitive Advantage is unable to moderate Leverage's relationship to Environmental Disclosure.